Strategy for Socialization of New Political Parties Ahead of the 2024 General Election (Case Study of the Gelora Party) - Zainul Djumadin (SEAN Institute, 2023)
Ahead of the 2024 general election, political parties in Indonesia have started carrying out activities so that their political parties are known to many people. The Indonesian People's Wave Party or Gelora is a new political party that was founded in 2019 and will participate in the election for the first time in 2024. This research discusses the socialization strategies for new political parties ahead of the 2024 elections. The aim of this research is to find out what socialization strategies are used by the Indonesian People's Wave as a new political party that will participate in the 2019 elections. The approach used in this research is qualitative and the method used is phenomenology. Data collection carried out was in-depth interviews and document study. The results of this research were the findings of nine themes, namely as follows: Face to face, social media, community service, young people, planning and assignments, self-introduction, adjusting style, mindset, and creating content.